2011
DOI: 10.4103/2230-8210.83396
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying existing premix therapy (BIAsp 30) with BIAsp 50 and BIAsp 70: A consensus statement

Abstract: In 2009, consensus guidelines were published on intensification of insulin therapy using the premix analog biphasic insulin aspart (BIAsp) 30 in the treatment of type 2 diabetes, based on the recommendations of an international, independent expert panel. The guidelines included recommendations and titration algorithms for intensification from basal insulin once (OD) or twice daily (BID) to BIAsp 30 BID, from OD BIAsp 30 to BID, and from BID BIAsp 30 to three times daily (TID). Building on these recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Our findings are consistent with previous reports that BIAsp therapy can be intensified safely 4,20 . Both RCTs and observational studies have shown that improved glycemic control can be achieved without increasing hypoglycemia by increasing the frequency of daily dosing with BIAsp 30 29,30 or by switching to BIAsp 50 three-times daily 31 .…”
Section: Discussionsupporting
confidence: 95%
“…Our findings are consistent with previous reports that BIAsp therapy can be intensified safely 4,20 . Both RCTs and observational studies have shown that improved glycemic control can be achieved without increasing hypoglycemia by increasing the frequency of daily dosing with BIAsp 30 29,30 or by switching to BIAsp 50 three-times daily 31 .…”
Section: Discussionsupporting
confidence: 95%
“…Of the 35 studies, there were two systematic reviews or meta-analyses [ 12 , 13 ], 19 RCTs [ 14 – 32 ] (including three crossover studies [ 19 , 25 , 28 ]), two post hoc analyses of pooled data from RCTs [ 33 , 34 ], ten prospective, nonrandomized, observational or interventional studies [ 35 – 44 ], one retrospective observational study [ 45 ], and one consensus statement [ 9 ] (Table S1 in the ESM). Sample sizes ranged from 13 [ 42 ] to 744 [ 23 ]; overall, the studies enrolled more than 6000 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have published clinical guidance on the use of low-mix insulin analogs [ 7 , 8 ]. However, to our knowledge, only one group has made clinical recommendations on the use of mid-mix (or high-mix) premixed analogs [ 9 ]. These recommendations, published in 2011 as part of a consensus statement, rely on clinical evidence from just four studies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ratio premixes, such as 50% soluble rapid-acting insulin/50% protaminated insulin, are also available and can be useful for patients with specific needs (e.g., patients with very high PPG values or problems with hypoglycemia). For information on intensifying to higher ratio premix insulin analogs, refer to the published guidance [ 43 ].…”
Section: Recommendationsmentioning
confidence: 99%